The politics of justifying force : the Suez Crisis, the Iraq War, and international law - Peevers, Charlotte (Oxford University Press, 2013)
What are the politics involved in a government justifying its use of military force abroad? What is the role of international law in that discourse? How and why is international law crucial to this process? And what role does the media have in mediating the interaction of international law and politics? This book provides a fresh and engaging answer to these questions. It introduces different actors to the study of international law in this context, in particular highlighting theimportance of institutional actors and the role of the media. It takes a theoretical approach, informed by detailed.